Bioinformatics Analysis Of Novel Non-Coding Motifs In Pathogenic Bacterial Genome - Shayala, Nishat; Rashid, Ishtiaque (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Antibiotic resistance of MRSA (Methicillin Resistant Staphylococcus aureus) has been evolved through the rapid and diversified changes in the genetic structure of the bacterial strains. The onset of new resistant strains makes the diagnosis, prognosis, treatment and control process more difficult. The study was started with MRSA252, the most diverse strain of S. aureus and then elaborated to 14 other strains. By screening out the complete genome sequences of MRSA, 274 regions of 362,792bp non-coding unique sequences were found. Among those, sequences of less than 500bp length are mostly important to use in diagnostic purposes. Functional analysis and comparison with few other pathogens were done to find correlations. J. Asiat. Soc. Bangladesh, Sci. 39(1): 9-20, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16028